Design and Development of Gain Scheduling PID and Fuzzy-PID Control for DC Motor Speed Based on MATLAB Simulink - Bambang Supriyo; Marshanda Aprilian Nisha; Keisya Djenar Dinda Lestari; Vinda Setya Kartika (JAICT, 2026)
Speed control of DC motors plays an important role in industrial applications because it directly affects system performance and efficiency. Conventional PID controllers are widely used; however, they have limitations in handling setpoint changes and varying system dynamics. Previous studies have shown that adaptive methods such as Gain Scheduling PID and Fuzzy-PID can improve control performance, but comparative studies under varying setpoints remain limited. Therefore, this research aims to design and analyze the performance of Gain Scheduling PID and Mamdani-based Fuzzy-PID controllers for DC motor speed control using MATLAB Simulink. The research method includes DC motor modeling, controller design, simulation under setpoint variations from 2000 to 8000 RPM, and performance analysis based on rise time, overshoot, settling time, and steady-state error. The results indicate that both controllers are capable of regulating DC motor speed effectively; however, the Fuzzy-PID controller provides a more adaptive transient response with lower overshoot and steady-state error at certain operating conditions compared to the Gain Scheduling PID controller.